Ribotyping of Clostridium difficile strains associated with nosocomial transmission and relapses in a Swedish County. Issue 2 (25th July 2012) - Magnusson, Cecilia; Wullt, Marlene; Löfgren, Sture; Iveroth, Peter; Åkerlund, Tomas; Matussek, Andreas
<x xml:space="preserve">Abstract</x> Clostridium difficile is an emerging threat in hospital environments. To analyse possible transmission and to distinguish between relapse and reinfection a collection of C. difficile isolates, sampled from 162 consecutive episodes of C. difficile infection, were PCR ribotyped. Two ribotypes (001 and 012) were prone to cause nosocomial acquisition. Moreover, ribotype 001 had a tendency to cause relapses as almost one in two patients with this ribotype had one or more relapses. By using PCR ribotyping strains inclined to cause relapses and strains associated with hospital transmission might be detected. This enables optimized hygiene measures and may improve the choice of treatment regimen.